Cartilla didáctica para las pymes del departamento del meta acerca de la conceptualización aduanera para exportación (2021)
The customs concept for exports covers concepts, laws and processes carried about regarding business and commercial matter. On the other hand, small organizations cover a great deal of the national economy being of big importance without getting the importance it should, asides from lack of training and reach it is needed related to customs to accomplish international exchanges acquiring a better ground.